Surgical aspects of renal carcinoma - Bonavita Páez, Luis; Garcia Guido, Luis; Garcia Guido, Luis; Maquieira, Gonzalo; Pereyra Bonasso, Jorge; Praderi, Raúl C.; Delgado Pereira, Hugo; Martínez, José Luis (Cirugía del Uruguay, 1982)
When dealing with the surgical aspects of renal carcinonoma, we chose the chapters that in our opinion arouse the greatest concern and interest to both urologists and general surgeons.